The Planner's Guide to Natural Resource Conservation: The Science of Land Development Beyond the Metropolitan Fringe - Esparza, Adrian X.; McPherson, Guy.; SpringerLink (Online service) (New York, NY : Springer New York, 2009)
Much of the country's recent population growth is situated beyond the metropolitan fringe, where development consumes millions of acres of privately owned land. Exurbanization has become the dominant pattern of land development in America and there is no indication it will slow in the future. This development depletes agricultural and wildlands, and causes numerous environmental impacts ranging from the loss of biodiversity and wildland habitats to soil erosion, an increase in nonnative species, and the heightened threat to endangered species. Written for regional planners, planning commissions, local elected officials, environmental groups, and the public-at-large, The Planner's Guide to Natural Resource Conservation provides readers from diverse, nonscientific backgrounds with a working knowledge of how and why exurbanization impacts environmental systems. Contributors include experts in rangeland ecology, restoration ecology, zoology, urban and regional planning, and conservation biology, who highlight the best practices to mitigate environmental problems or to avoid them altogether. Each chapter will leave readers with a firm grasp of relevant concepts and processes, an understanding of current research, and the know-how to apply science to land-use decisions. Adrian X. Esparza is Associate Professor in the School of Natural Resources at the University of Arizona (Ph.D. 1987, University of Illinois-Urbana). He taught previously in the School of Planning, College of Architecture at the University of Arizona. His research focuses on exurban land development in the southwest United States and urbanization in the United States-Mexico border region. He has published dozens of articles in the fields of urban and regional planning and regional science. Guy McPherson is a Professor in the School of Natural Resources at the University of Arizona (Ph.D. 1987, Texas Tech University). He also worked for the University of Georgia, Texas A & M University, University of California-Berkeley, and The Nature Conservancy. His research focuses on development and application of ecological knowledge. His scholarly efforts have produced dozens of journal articles and eight books.
SECTION 1: HISTORY AND FUNDAMENTAL ECOLOGICAL CONCEPTS -- Exurbanization and Aldo Leopold's Human-Land Community -- Fundamental Concepts in Ecology -- Climate Change and Ecology in Rural Lands -- SECTION 2: EXURBAN LAND DEVELOPMENT, HABITAT AND WILDLIFE -- Biodiversity and Residential Development Beyond the Urban Fringe -- Wildlife Corridors and Developed Landscapes -- Exurban Land Development and Breeding Birds -- Integrating Wildlife Conservation into Land-Use Plans for Rapidly Growing Cities -- Into the Wild: Vegetation, Alien Plants, and Familiar Fire at the Exurban Frontier -- SECTION 3: WATER RESOURCES, WETLANDS AND STORM WATER MANAGEMENT -- Impacts of Exurban Development on Water Quality -- Preparing for Human Expansion into Exurban Riparian Areas -- Storm Water Management in Exurbia -- SECTION 4: SCIENCE-BASED PLANNING IN EXURBAN AREAS -- A Science-Based Approach to Regional Conservation Planning -- Mitigating Environmental Problems in Exurban Development: An Overview of Rural-Specific Planning Devices.
Keywords: ENVIRONMENTAL SCIENCES; LANDSCAPE ECOLOGY; ECOLOGY; CONSERVATION BIOLOGY; URBAN ECOLOGY; NATURE CONSERVATION; SUSTAINABLE DEVELOPMENT; ENVIRONMENT; NATURE CONSERVATION; LANDSCAPE ECOLOGY; COMMUNITY & POPULATION ECOLOGY; CONSERVATION BIOLOGY/ECOLOGY.; URBAN ECOLOGY; SUSTAINABLE DEVELOPMENT